Does cardiovascular comorbidities are important as far as ophthalmology treatment is concerned? - Wełnicki, Marcin; Mamcarz, Artur (Klinika Oczna / Acta Ophthalmologica Polonica, 2012)
Majority of patients with glaucoma, age-related maculopathy or diabetic macular edema is old. Therefore arterial hypertension, coronary arterial disease, diabetes and dyslipidemia are common finding in patients with sick eye. In this article some situations needing cooperation of cardiologist and ophthalmologist have been pointed. The influence of treatment of hypertension on glaucoma outcomes and the influence of intraocular injections of biological drugs on cardiovascular risk seems to be the most important issues.